Evaluation of Cognitive Process Dimension of TEOG and LGS Central Exam Science Questions with Revised Bloom Taxonomy - Merve POLAT; Elif BİLEN (Journal of the Turkish Chemical Society Section C Chemical Education, 2022)
Central exams have a decisive role in making important decisions about the education process, such as placing students in some programs, deciding on their educational progress, determining the performance of teachers and school success levels. In this study, it was aimed to analyze and evaluate a total of 240 science questions in the central exams (Basic Education to Secondary Education Exam-TEOG and Entrance System for High Schools-LGS) applied between 2013 and 2021 according to the cognitive process dimension of the Revised Bloom Taxonomy (RBT). The data were obtained through document analysis, which is one of the qualitative research methods. According to the findings of the study, it was determined that 227 questions (94.58%) in TEOG and LGS exams are at low level, and 13 questions (5.42%) are at high level cognitive steps. According to the obtained findings, it was seen that the questions were not distributed proportionally to the cognitive steps, and were insufficient in measuring especially high-level skills. Removing of this deficiency in the central exams that concern the whole country will be beneficial for the high-level cognitive development of students. In this context, it is recommended to determine the objectives first, then to create taxonomies that will guide the objectives, and finally to consider the RBT) table while preparing the exam questions.